Minimum Wage and Job Mobility in Peru - Cespedes, Nikita (2014)
We study the effects of the minimum wage over employment and income in Peru by considering a monthly database that captures seven minimum wage changes registered between 2002 and 2011. We estimate that about 1 million workers earn an income by main occupation in the neighborhood of the minimum wage. Findings show that the minimum wage-income elasticity is statistically significant; the evidence also suggests that those who receive low incomes and those working in small businesses are the most affected by increases in the minimum wage. Employment effects are monotonically decreasing in absolute terms by firm size: they are moderate in large firms and higher in small firms. Results are robust when assessing the job-to-job transitions. Finally, we present evidence that supports the hypothesis that the minimum wage in Peru is correlated with income. The movement of income distribution in the context of changes in the minimum wage and the results provided by a model that captures the drivers of income justify this finding.